2005
DOI: 10.1590/s0004-27302005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Papel da vitamina D na função neuro-muscular

Abstract: RESUMOA vitamina D, através de suas ações no intestino, rim, osso e glândulas paratiróides, é um hormônio fundamental para a homeostase do cálcio e para o desenvolvimento de um esqueleto saudável. Além disso, receptores deste hormônio podem ser encontrados em quase todos os tecidos do organismo e outras ações não relacionadas ao metabolismo mineral têm sido imputadas a ele. Na célula muscular esquelética, a vitamina D atua através do mecanismo clássico de ligação a um receptor nuclear e também através da ligaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
0
4
0
15
Order By: Relevance
“…Then, vitamin D3 goes back into the bloodstream to the kidneys and, mediated by the enzyme hydroxylase, forms 1,25-dihydroxyvitamin D or calcitriol. This renal action is controlled by several factors, unlike the previous stage, in the liver, which is poorly regulated 10,11 ( Figure 3). Vitamin D acts in the control of plasma calcium levels, after its absorption in the intestinal tract, aiding in the regulation of bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Then, vitamin D3 goes back into the bloodstream to the kidneys and, mediated by the enzyme hydroxylase, forms 1,25-dihydroxyvitamin D or calcitriol. This renal action is controlled by several factors, unlike the previous stage, in the liver, which is poorly regulated 10,11 ( Figure 3). Vitamin D acts in the control of plasma calcium levels, after its absorption in the intestinal tract, aiding in the regulation of bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…O efeito não-genômico é rápido e mediado pela ligação da membrana com o receptor de vitamina D (VDR) (Pfeifer et al 2002, Ceglia 2008. Embora haja referência à presença do VDR no músculo esquelético (Pedrosa & Castro 2005), parece que os níveis de expressão desse receptor são baixos, uma vez que não são observadas lesões nesse tipo de tecido. Através da imuno-histoquímica, constatou-se que, na musculatura lisa das artérias e do sistema digestivo, parte das células têm VDR, enquanto outras não os possuem (Barros 2011).…”
Section: Metabolismounclassified
“…Several studies have shown that vitamin D metabolites affect muscle cell metabolism through various pathways: by mediating gene transcription, through rapid pathways not involving DNA synthesis and by the allelic variant of the VDR (40). Both in animal models and in humans, a VDR has been found in skeletal muscle cells that specifically binds 1,25(OH) 2 D 3 .…”
Section: Muscle Functionmentioning
confidence: 99%